PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS GIMKIT PADA MATA PELAJARAN EKONOMI UNTUK MENINGKATKAN PEMAHAMAN BELAJAR SISWA FASE F SMAN 12 KOTA JAMBI - Ortawita Andesta; Arpizal; Nurmala Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by students’ low learning comprehension in Economics, particularly on taxation material, at SMA Negeri 12 Kota Jambi, as well as the use of conventional learning media that made the learning process less interactive and engaging. Therefore, this study aimed to develop Gimkit-based learning media, examine its feasibility, and determine its effectiveness in improving students’ learning comprehension. This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research was conducted at SMA Negeri 12 Kota Jambi. Data were collected through media expert and material expert validation sheets, as well as students’ learning comprehension tests using a one-group Pre-Test and Post-Test design. The validation data were analyzed using descriptive quantitative analysis, while the effectiveness data were analyzed using the N-Gain score. The results showed that the Gimkit-based learning media was highly feasible, obtaining validation scores of 98.75% from the media expert and 87.50% from the material expert. Students’ average score increased from 58.37 in the Pre-Test to 91.49 in the post-test, with an N-Gain score of 0.79 in the high category. These findings indicate that Gimkit-based learning media is both feasible and effective in improving students’ learning comprehension of taxation material while promoting a more interactive and enjoyable learning experience.